Delinquent Behavior: An Analysis of Albert Bandura’s Social Learning Theory - Astrid Oktaria Audra Siregar; Diah Karmiyati (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
The phenomenon of delinquent behavior that is usually carried out by adolescents is skipping school to drug use and murder. One of the causes is the wrong modeling from the environment so that adolescents implement it into deviant behavior. The purpose of the research in this article is to understand the social learning theory of modeling by Albert Bandura and its implementation. The application of social learning in the learning process is by looking at the social environment as a learning tool. The method used for this research is library research by collecting data relevant to the theme from books, journals, articles and others without conducting a review of the field. On the basic assumption of the theory used, Albert Bandura's learning theory, there is a cognitive process in adolescents that plays a role in learning and learning occurs due to the influence of the social environment.